Religion, Customs, and Village Government in Collaborating the Pillars of Rural Development - Yulius Luturmas (PT Mattawang Mediatama Solution, 2022)
This research is entitled Collaborative Pillars of Rural Development, which is located in Latdalam Village, South Tanimbar District, Tanimbar Islands Regency, Maluku Province. With a qualitative descriptive model, researchers took field data to obtain scientific facts related to How Collaborative Pillars Drive Latdalam Village Development. And the results of this study are (1) the communication of the driving pillars of village development in the village of Latdalam (Village Government, Churches, and Customary Institutions) needs to be maximized; (2) Commitment from the driving pillars and the community needs to be implemented with high development and awareness, and suggestions are given to this problem, namely: Implementation of the concept of Collaborating the village driving pillars in Latdalam, because healthy collaboration will create healthy ones, and be an example which is good for the next generation to maintain and develop the concept of collaboration in subsequent developments.